Serum Level of Relaxin-2 Correlated to the Diabetic Patients with Coronary Artery Disease - Huda S.Abdulghani; Sura A. Abdulsattar; Essam N.Salman (International Journal of Psychosocial Rehabilitation, 2020)
Relaxin has Vasodilatory effects of cardiovascular complication of diabetes through promotes flow and vasodilation in coronary arteries. This study aim to evaluate of relaxin as a biomarker for cardiovascular complication of diabetes. The study included88 Iraqi subjects and divided into three groups: (29) Type 2 diabetes mellitus patients and (29) diabetic patients with CAD compared with (30) healthy person. Serum relaxin-2 was determined by an enzyme immunoassay for quantitative in vitro diagnostic measurement using kit manufactured by Mybiosource (ELIZA kit), insulin by Demeditec (ELIZA kit) and Blood sugar profile including fasting blood sugar and HbA1c were done by Roche/Hitachi cobas c 311device. The mean ± SD of serum Relaxin-2 (pg/ml) of type 2 diabetic (20.65±4.14) and diabetic with CAD(17.95±5.18) patients levels showed a significant decrease (p<0.05) in comparison to that level in control group (24.28±7.31). Meanwhile Relaxin-2 level in diabetic patients with CAD demonstrate a highly significant decrease (p<0.01) in comparison to that level of control group. However, there is no significant differences (p≥0.05) between T2DM and diabetic with CAD in compare to each other. We concluded that there was a negative correlation between Relaxin-2 and FBS in diabetic patients with CAD.